Interleukin-6 Is Required for Pancreatic Cancer Progression by Promoting MAPK Signaling Activation and Oxidative Stress Resistance - Zhang, Yaqing; Yan, Wei; Collins, Meredith A.; Bednar, Filip; Rakshit, Sabita; Zetter, Bruce R.; Stanger, Ben Z.; Chung, Ivy; Rhim, Andrew D.; di Magliano, Marina Pasca (American Association for Cancer Research, 2013)
Pancreatic cancer, one of the deadliest human malignancies, is almost invariably associated with the presence of an oncogenic form of Kras. Mice expressing oncogenic Kras in the pancreas recapitulate the stepwise progression of the human disease. The inflammatory cytokine interleukin (IL)-6 is often expressed by multiple cell types within the tumor microenvironment. Here, we show that IL-6 is required for the maintenance and progression of pancreatic cancer precursor lesions. In fact, the lack of IL-6 completely ablates cancer progression even in presence of oncogenic Kras. Mechanistically, we show that IL-6 synergizes with oncogenic Kras to activate the reactive oxygen species detoxification program downstream of the mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) signaling cascade. In addition, IL-6 regulates the inflammatory microenvironment of pancreatic cancer throughout its progression, providing several signals that are essential for carcinogenesis. Thus, IL-6 emerges as a key player at all stages of pancreatic carcinogenesis and a potential therapeutic target. © 2013 AACR.